Halal Tourism in West Sumatra Province: An Implementation of Sharia Compliance and Minangkabau Custom - Cipta, Hendra; Hatamar, Hatamar; Indrawati, Indrawati; Makmun, Sukran (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
This study aims to examine the implementation of Sharia compliance and Minangkabau custom in the halal tourism industry in West Sumatra, which is a leading province in Indonesia’s halal tourism sector. The research methodology used in this study is a qualitative descriptive, with in-depth interviews serving as the primary data collection instrument. The Indonesian Ulema Council, the Provincial Tourism Office and the halal tourism managers in the provinces of West Sumatra are the main sources of data for this study and purposive sampling strategies are used in this study to pick informants based on criteria. The findings of this study indicate that the halal tourism industry in West Sumatra substantially complied with the Sharia rules outlined in the fatwa of the Indonesian Ulema Council No. 108 of 2016 due to the implementation of Sharia compliance in halal tourism in this province through the Minangkabau custom adat basandi syarak, syarak basandi kitabullah by combining religious and cultural values that are deeply rooted in society, this saying is ingrained in the life of the Minang people. This is what distinguishes West Sumatra from other provinces in maintaining Sharia compliance within the halal tourism industry. Penelitian ini bertujuan untuk melihat aktualisasi kepatuhan syariah dan budaya adat Minangkabau pada industri wisata halal di Sumatera Barat, sebagai provinsi terdepan dalam sektor wisata halal di Indonesia. Metodologi penelitian yang diaplikasikan pada riset ini adalah metodologi deskriptif kualitatif dengan wawancara mendalam sebagai instrumen yang digunakan dalam pengumpulan data riset. Sumber data primer penelitian ini adalah Majelis Ulama Indonesia, Dinas Pariwisata Propinsi dan para pengelola pariwisata halal yang ada di Propinsi Sumatera Barat. Kriteria pemilihan informan pada penelitian ini berdasarkan teknik purposive sampling. Temuan riset ini menunjukkan bahwa di Sumatera Barat industri wisata halalnya secara substantif sudah mematuhi aturan syariah sebagaimana yang sudah ditetapkan Majelis Ulama Indonesia melalui fatwa No. 108 Tahun 2016, hal ini karena implementasi nilai-nilai syariah pada industri halal tourism di provinsi ini seiring dengan pepatah budaya Minang yang berbunyi adat basandi syarak, syarak basandi kitabullah. Pepatah ini adalah wujud harmonisasi nilai-nilai agamis dan budaya yang sudah kuat berakar dalam sendi kehidupan masyarakat, pepatah ini juga sudah dikenal turun-temurun oleh anak kemenakan di Minang. Hal inilah yang membedakan Sumatera Barat dengan provinsi lain dalam menjaga kepatuhan syariah wisata halal.